Herding behaviour by South African unit trusts in the consumer services sector - Abramson, Simone Nicole (Department of Finance and Tax, 2017)
This study examines whether there is herding by general equity unit trusts as investors in the consumer services sector in South Africa. It also investigates whether herding was more prevalent during the financial crisis period in South Africa between 2008 and 2010, than during a non-crisis period. Using a herding measure developed by Lakonishok, Shleifer and Vishny (1992) (LSV), it was found that there was indeed herding behaviour by general equity unit trusts in the consumer services sector. A herding rate (i.e. the proportion of trades by general equity unit trusts in the consumer services sector in excess of the expected random and independent proportion) of 7.75% is calculated. Possible reasons for herding in the consumer services sector include; consumer services companies being profitable investments and a small number of investment analysts in South Africa. It was also observed that herding behaviour was not more prevalent during the financial crisis period (12.14%) than the non-crisis period (6.36%), as these two periods were not statistically different from one another, even though the average herding rates differed.